Sustainable Regional Development Strategy for Dealing with the Distribution of Landfill Points in West Lombok Regency - Fadilah, Iqbal Nugraha; Munawir, Abdillah (ASTONJADRO, 2024)
In order to address the distribution of rubbish accumulation points, this study intends to perform a spatial analysis of the distribution of garbage accumulation points and to establish a sustainable regional development strategy. It is anticipated that the study's findings will be input and evaluation materials for regional planners in improving regional planning that is more responsive and adaptive. Waste is an environmental problem that must be addressed in urban areas, including in West Lombok Regency, which faces the distribution of garbage accumulation points. This study uses Geographic Information System and Strengths, Weaknesses, Opportunities, and Threats methods, with field survey techniques, secondary data analysis, and literature study. The sustainable regional development tactics that are possible to implement include: (1) Raising public awareness of the significance of environmental preservation; (2) Making policy support from local governments such as tax incentives or sanctions for businesses or individuals who still pollute the environment; (3) Developing infrastructure such as integrated landfills, recycling facilities, and waste treatment.